Cholecalciferol complexation with hydroxypropyl-β-cyclodextrin (HPBCD) and its molecular dynamics simulation. (21st April 2022) - Wang, Fang; Yu, Wenbo; Popescu, Carmen; Ibrahim, Ahmed Ashour; Yu, Dongyue; Pearson, Ryan; MacKerell, Alexander D.; Hoag, Stephen W.
Abstract: The focus of the current study is to investigate cholecalciferol (vitamin D3) solubilization by hydroxypropyl-β-cyclodextrin (HPBCD) complexation through experimental and computational studies. Phase solubility diagram of vitamin D3 (completely insoluble in water) has an AP profile revealing a deviation from a linear regression with HPBCD concentration increase. Differential scanning calorimetry (DSC) is the best tool to confirm complex formation by disappearance of cholecalciferol exothermic peak in cholecalciferol–HPBCD complex thermogram, due to its amorphous state by entering HPBCD inner hydrophobic cavity, similarly validated by Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). AP solubility diagram profile can be associated with cholecalciferol–HPBCD complex instability in liquid phase requiring spray drying to bring it to a solid dispersion state (always more stable) illustrated by scanning electron microscopy (SEM). Computational studies led to a deeper understanding and clarification, at molecular level, of the interactions within cholecalciferol–HPBCD complex. Thermodynamics and geometry of the complex were investigated by molecular dynamics (MD) simulation.